2,6-bis(5-(tert-butyl)-1H-pyrazol-3-yl)pyridine: effects of the peripheral aliphatic side chain on the coordination of actinides(III) and lanthanides(III) - Stracke, Jonas; Weßling, Patrik; Sittel, Thomas; Adam, Christian; Rominger, Frank; Geist, Andreas; Panak, Petra (Inorganic chemistry, 2024)
To improve our understanding of the interaction mechanism in trivalent lanthanide and actinide complexes, studies with structurally different hard and soft donor ligands are of great interest. For that reason, the coordination chemistry of An(III) and Ln(III) with 2,6-bis(5-(tert-butyl)-1H-pyrazol-3-yl)pyridine (C4-BPP) has been explored. Time-resolved laser fluorescence spectroscopy (TRLFS) studies have revealed the formation of [Cm(C4-BPP)n]3+ (n = 1-3) (log β1′ = 7.2 ± 0.4, log β2′ = 10.1 ± 0.5, and log β3′ = 11.8 ± 0.6) and [Eu(C4-BPP)m]3+ (m = 1-2) (log β1′ = 4.9 ± 0.2 and log β2′ = 8.0 ± 0.4). The absence of the [Eu(C4-BPP)3]3+ complex shows a more favorable complexation of Cm(III) over that of Eu(III). Additionally, complementary NMR measurements have been conducted to examine the M(III)-N bond in Ln(III) and Am(III) C4-BPP complexes. 15N NMR data have revealed notable differences in the chemical shifts of the coordinating nitrogen atoms between the Am(III) and Ln(III) complexes. In the Am(III) complex, the coordinating nitrogen atoms have shown a shift by 260 ppm, indicating a higher fraction of covalent bonding in the Am(III)-N bond compared with the Ln(III)-N bond. This observation aligns excellently with the differences in the stability constants obtained from TRLFS studies.
Gesehen am 21.10.2024